A Dance with Many Secrets: The Experience of Emotional Harm from the Perspective of Past Professional Female Ballet Dancers in Canada - Moola, Fiona; Krahn, Alixandra (Journal of Aggression, Maltreatment & Trauma, 2018)
Originating in the Italian and French courts, ballet is an age-old art that fuses aesthetics and athleticism (Wulff, 2008). Despite changing times, ballet masters and mistresses tenaciously hold on to a sense of deep traditionalism. However, some scholars suggest that unwavering devotion to the art may conceal troubled embodied relations and oppressive practices (Gvion, 2008). In this study, we drew on the phenomenological research tradition in an effort to further examine the power relations that play out on the body in the world of Canadian professional ballet (Papaefstathiou, Rhind, & Brakenridge, 2013). Twenty past professional female ballet dancers from across Canada participated in this study. Our dedicated dancers were relentless. They sacrificed body and mind in the pursuit of excellence in a broader cultural context that expected nothing less. The dancers normalized harmful emotional experiences, inappropriate sexual transgressions, and chronic injury (Gvion, 2008). They also described experiences of neglect—and feeling replaceable—after the onset of injury. We have attempted to theorize our findings within the context of embodiment literature and the work of gender theorists. Emboldened by our dancers’ voices, we have shed light—and broken secrets—regarding some of the harmful practices that still characterize professional ballet in Canada. We hope that our work might further continue efforts to democratize power imbalances in professional ballet and ultimately enhance holistic dancer development and health.
Publisher: Routledge _eprint: https://doi.org/10.1080/10926771.2017.1410747